Salt crystallization in plastered or rendered walls - Gonçalves, T. D. (2014)
This thesis was aimed at understanding the behaviour of plasters and renders on salt-loaded walls. The current state-of-the-art and state-of-the-practice were accessed focusing particularly on old plastered/rendered buildings and their conservation practice in Portugal. Afterwards, experimental work was carried out aiming at answering the identified questions. Two laboratory techniques, for relative humidity control with salt solutions and for salt content determination by hygroscopic moisture content measurements, were investigated. Drying of salt-loaded materials was studied by means of drying experiments monitored using a magnetic resonance imaging (MRI) technique. The behaviour of plasters and renders in relation to salt crystallization was then accessed by means of crystallization tests and MRI-monitored drying tests. Most drying and crystallization tests were carried out on specimens composed by a plaster or render applied on a given substrate. Finally, the study of five old buildings in Portugal provided an insight into practice-related salt decay features. On the basis of this research, guidelines are proposed to select plasters and renders for salt loaded walls. Conclusions were also achieved on: (i) possibilities and limitations of the test methods, particularly salt crystallization tests, and diagnostic methodology used; (ii) salt decay processes, namely, influence of soluble salts on drying, mechanisms of salt-induced dampness and salt distribution in masonry; (iii) reasons for sodium chloride being typically much less damaging than sodium sulfate in laboratory tests; (iv) influence of factors such as the type of salt, kind of substrate material or presence of a paint layer on the behaviour of plasters and renders; (v) factors that can account for a worsening of salt damage after restoration interventions; (vi) field or application conditions that favour salt damage.